Analisis Pelaksanaan Sistem Keuangan Berbasis Web Menunjang Kinerja Kelurahan Duren Tiga di Kecamatan Pancoran - Dwi Ratnasari; Dodi Rahmat Setiawan (Jurnal Ilmu Administrasi Publik, 2021)
Duren Tiga Village, Pancoran District, South Jakarta Administrative City is a Regional Performance Unit (SKPD) of DKI Jakarta Province. The method used in this study is a qualitative approach. Data collection techniques are carried out by observation, interview and documentation techniques. The research informants were 1 (one) Secretary of Duren Tiga Village, 1 (one) Head of Duren Tiga Village Section, 1 (one) Treasurer of Duren Tiga Village, 1 (one) Non ASN / Honorary Staff and 1 (one) Academic. The results of the study show that (1) The implementation of the Web-Based Financial System in Duren Tiga Village is very influential on employee performance. (2) Constraints found in implementing a web-based financial system in Duren Tiga Village are Internet Network Connection, Error System and Employee Performance (3) Efforts made to deal with obstacles found in the Duren Tiga Village Financial System Implementation are the provision of facilities adequate, smooth internet network connection and good employee cooperation and coordination.